The Effect of Discovery Learning and Direct Instruction on EFL Learners with Different Learning Styles - Munfa'ati, Heny; Mujiyanto, Januarius; Suwandi, Suwandi (English Education Journal, 2020)
This study is experimental research with a factorial design which aimed to find out the effect of discovery learning and direct instruction on EFL learners with different learning style (The Tenth Graders of SMA Negeri 15 Semarang). The samples of the study were tenth graders of SMA Negeri 15 Semarang in the 2018/2019 academic year. There were two classes, experimental class I and experimental class II which every class consisted of 20 students. Direct Instruction method was used in the experimental class I, while Discovery Learning method was used in experimental class II. To know-how is the effect of direct instruction to visual and auditory and how is the effect of discovery learning to visual and auditory, T-test was used. To know-how is the difference in the achievement between visual and auditory by using direct instruction and discovery learning, students’ mean scores in experimental classes I and II were compared. While two-way ANOVA with F-test at the 5% (0.05) level of significance was used to know how significant relationships among the methods and the learning style. The result of this study showed that direct instruction and discovery learning methods are effective to be used in teaching writing for visual and auditory learning style students. There were no significant differences in achievement between visual and auditory learning style students using direct instruction and discovery learning methods. For the interaction among the variables, it shows that there was no interaction among the methods, students’ learning style, and students’ writing skill.